All I see is part of me - Curtis, Chara M., 1951-; Aldrich, Cynthia, 1947- (Bellingham, WA : Illumination Arts Pub. Co., 1989)
A little boy discovers that all of creation is a part of him and he is a part of all creation.
Keywords: Stories in rhyme; Self-perception -- Fiction